The Effectiveness of Realistic Mathematics Learning in Improving Students' Understanding of Mathematics Concepts in Grade 3 of SDIT Al-Kautsar Cikarang - Santoso, Gabriell Batistuta; Santosa, Donald Samuel Slamet (Institut of Shanti Bhuana, 2024)
This study begins with the problem of lack understanding of mathematics learning concepts in SDIT Al-Kautsar Cikarang students. This causes student learning outcomes to be not optimal. Therefore, this study aims to test the effectiveness of Realistic Mathematics learning in improving the understanding of mathematical concepts of grade 3 students of SDIT Al-Kautsar Cikarang. The method used in this research is Pre-Experimental Design with One-Group Pretest-Posttest Design model. The data were analyzed through T-test (Paired Sample T-Test) and effectiveness test (N-Gain Score Test). The object of research is third grade students (3C) SDIT Al-Kautsar Cikarang, which amounted to 20 students. Data were collected through pre-test and post-test results. The results showed that the Sig. (2-tailed) on the Paired Sample T-Test analysis was 0.000, or less than 0.05. The average score also shows that the post-test results have an average score of 55.5, compared to the pre-test score of 89.2. The N-Gain Score test results based on the effectiveness criteria interpreted from the normality gain value show a value of 0.77, or more than 0.7. Based on this, it can be concluded that Realistic Mathematics is effective in improving students' understanding of mathematical concepts.